A Developmental Transcriptome Map for Allotetraploid Arachis hypogaea - Clevenger, Josh; Chu, Ye; Scheffler, Brian; Ozias-Akins, Peggy (Frontiers in Plant Science, 2016)
The advent of the genome sequences of Arachis duranensis and Arachis ipaensis has ushered in a new era for peanut genomics. With the goal of producing a gene atlas for cultivated peanut (Arachis hypogaea), 22 different tissue types and ontogenies that represent the full development of peanut were sequenced, including a complete reproductive series from flower to peg elongation and peg tip immersion in the soil to fully mature seed. Using a genome-guided assembly pipeline, a homeolog-specific transcriptome assembly for Arachis hypogaea was assembled and its accuracy was validated. The assembly was used to annotate 21 developmental co-expression networks as tools for gene discovery. Using a set of 8,816 putative homeologous gene pairs, homeolog expression bias was documented, and although bias was mostly balanced, there were striking differences in expression bias in a tissue-specific context. Over 9,000 alterative splicing events and over 6,000 non coding RNAs were further identified and profiled in a developmental context. Together, this work represents a major new resource for cultivated peanut and will be integrated into peanutbase.org as an available resource for all peanut researchers.